Fighting corruption through education in Indonesia and Hong Kong: comparisons of policies, strategies, and practices - Kamil, Dairabi; Mukminin, Amirul; Sheikh Ahmad, Ismail; Abu Kassim, Noor Lide (IIUM Press, International Islamic University Malaysia, 2018)
This study sought to compare the policies, strategies, practices and challenges of anti-corruption education (ACE) in formal education in Hong Kong and Indonesia. Data were collected through documentation, semi-structured interviews, and non-participant observations. The documents were analysed using Document Analysis tehnique, while data from interviews and observation were analyzed through the Constan Comparison method. The findings show that Indonesian ACE policies explicitly aim at formal education, while in Hong Kong they are part of prevention measures on educating the public of the evil of corruption. Both top-down and self-initiated ACE concurrently exist in Indonesia,while in Hong Kong it is mostly initiated by the Independendent Comission Against Corruption (ICAC). ACE in schools, in both contexts, includes curricular, extra and co-curricular strategies. The curricular ACE in Indonesia takes a considerable portion of the curriculum. Strong committment and preserverence for ACE seemed to characterize Indonesian informants of the institutions where ACE was self-initiated. Both Hong Kong and Indonesian informants expressed concern as regard the gap between ACE values taught to students in formal education and what they actually live in the society, and how best to present ACE in a way that appeals to the students.